CALL in a Climate of Change: Adapting to Turbulent Global Conditions – Short Papers From EUROCALL 2017 2017
DOI: 10.14705/rpnet.2017.eurocall2017.689
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of TTS as a pedagogical tool for pronunciation instruction: the ‘foreign’ language context

Abstract: Despite positive evidence demonstrating the pedagogical benefits of Text-To-Speech (TTS) synthesisers for second/foreign language learning (Liakin, Cardoso, & Liakina, 2017), there is a need for up-to-date formal evaluations, specifically regarding its potential to promote learning. This study evaluates the voice quality of a TTS system in comparison with a human voice, and examines its pedagogical potential for use in an English as a Foreign Language (EFL) setting in terms of speech quality, ability to be und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Recently, there have been studies that evaluate the voice quality of TTS systems, corroborating previous hypotheses that current synthesized voices are ready for use in L2 education: they are not only perceived as appropriate (or 'good enough') from a sound perspective (Bione, Grimshaw, & Cardoso, 2017;Cardoso, Smith, & Garcia Fuentes, 2015), but they are also more likely to enhance opaque features of the target language (e.g. regular past tense marking in English is often detected with higher accuracy in synthesized speech; Bione et al, 2017;John & Cardoso, 2017). One area that has not received consideration by researchers is TTS' ability to raise L2 learners' PA.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Recently, there have been studies that evaluate the voice quality of TTS systems, corroborating previous hypotheses that current synthesized voices are ready for use in L2 education: they are not only perceived as appropriate (or 'good enough') from a sound perspective (Bione, Grimshaw, & Cardoso, 2017;Cardoso, Smith, & Garcia Fuentes, 2015), but they are also more likely to enhance opaque features of the target language (e.g. regular past tense marking in English is often detected with higher accuracy in synthesized speech; Bione et al, 2017;John & Cardoso, 2017). One area that has not received consideration by researchers is TTS' ability to raise L2 learners' PA.…”
Section: Introductionsupporting
confidence: 62%
“…in comparison with spontaneous production). These findings suggest that, considering these two measures, TTS constitutes a good source of aural input (as reported Cardoso et al, 2015 andBione et al, 2017), and that it may be used to enhance the opaque alternations found in past -ed marking in English (as hypothesized, based on Bione et al, 2017, andJohn &. We acknowledge some of the limitations of our study, particularly the limited number of participants and lack of statistical rigour in our analysis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Several studies have found potential benefits from using TTS in language classes or have found no significant differences between using a synthetic or human voice (Bione et al, 2017;Cardoso et al, 2015;Craig & Schroeder, 2019;Hillaire et al, 2019;Kang et al, 2008) and the possibility of more interactive models where people can keep conversations in real time with machines (Ku-mar et al, 2023). In addition, TTS systems may use various techniques to improve the quality and naturalness of the generated speech, such as adjusting the rhythm and intonation to match that of a human speaker or adding natural-sounding pauses and inflections.…”
Section: Assistive and Text-to-speech Technologymentioning
confidence: 99%
“…Therefore, the potential application of TTS may impact several language programs. Regardless of the potential benefits of implementing TTS in ESL settings (Bione et al, 2017;Cardoso et al, 2015;Craig & Schroeder, 2019;Hillaire et al, 2019;Kang & chatGPT, 2023), currently, the only discussion about TTS systems in the English major has centered on using them to read abstracts. No other language program in the university where this study took place has considered using TTS synthesis, and no attention has been paid to the use of computer-generated voices in educational settings, especially in ESL settings where listening materials are abundant but sometimes difficult to find or do not fully adapt to the course requirements.…”
Section: Introductionmentioning
confidence: 99%